The Los Alamos National Laboratory Molecular Opacity Project and the Photodissociation Isotopic Effects of H(2)(+)and D-2(+) - Zammit, M.; Savage, J.; Colgan, J.; Fursa, Dmitry; Bray, I.; Leiding, J.; Nisoli, C.; Fontes, C.; Kilcrease, D.; Hakel, P.; Timmermans, E. (ASTRONOMICAL SOC PACIFIC, 2018)
No Abstract Available